ESRA19-0130 A case report of a BI-level erector spinae plane catheter technique for extensive chest trauma. (30th August 2019) - Thompson, M; Hodson, G; Ashken, T; Ng, SC
Abstract : Background and aims: The morbidity and mortality associated with rib fractures are significant. Risk factors for a poor outcome are patient and injury related. Regional analgesia can play an important role in facilitating rehabilitation and reducing the morbidity associated with respiratory failure, immobility and opioids. In many centres, thoracic epidural analgesia is the standard of care for patients deemed at high risk of complications. There are, however, an increasing number of peripheral regional options, offering unilateral analgesia and a safer side effect profile. In multilevel fractures however, these alternatives to central neuraxial blockade may not produce enough spread for adequate analgesia. Methods: We report a case of successful pain management of fractures of left ribs three to nine using bi-level erector spinae plane catheters in a 93-year-old woman whose drug history included clopidogrel and was thus considered to have an absolute contraindication to central neuraxial blockade. She had multiple risk factors for poor outcome, such as her age, diabetes history, obesity and the extent of her injuries. Results: Using this technique, our patient was able to fully participate in her rehabilitation, breathe deeply and cough effectively from approximately 30 minutes after each top-up. Her pain scores improved from 4/4 to 1/4 at rest and from 4/4 to 2/4 on movement. Supplemental oxygen was no longer required. She suffered no complications and was successfully discharged from the pain service 7 days after admission. Conclusions: We now consider ESP catheters in all patients with chest trauma. We do not believe that this bi-level technique has been described before.